Irregular migration from Cambodia characteristics, challenges, and regulatory approach - Hing, Vutha (Philippine Journal of Development)
The study examines the characteristics, root causes, and challenges of irregular migration from Cambodia and then discusses the regulatory approaches and policy options to manage it. It employed mixed approaches, including a survey of 507 households in six high-migration villages, focus group discussions with returned and intending migrant workers, and in-depth interviews with government officers, migration experts, and local community chiefs.